Reply to comment on: "On the effect of room temperature ageing of Ni-rich NiTi alloys". (October 2016) - Kustov, S.; Mas, B.; Kuskarbaev, Z.; Wang, X.; Van Humbeeck, J.
Abstract: Previous observations of unusual strong room temperature (RT) ageing effect in Ni-rich NiTi alloys are confirmed. We draw attention to our interpretations of the uncovered effect suggested in our previous work, which imply the involvement of defect-assisted rather than long-range bulk diffusion. New experimental results are presented which allow us to select sweeping-up of quenched-in defects by interfaces moving during martensitic transformation as the key ingredient of strong RT ageing. We link the uncovered effect with other manifestations of low-temperature (down to 15–20 K) diffusion of quenched-in defects in both twinned and faulted martensites, assisted by linear/planar structural elements of martensitic structures.